Inhibition of adipogenic differentiation of human SGBS preadipocytes by androgen-regulated microRNA miR-375. (15th October 2015) - Kraus, Matthias; Greither, Thomas; Wenzel, Carina; Bräuer-Hartmann, Daniela; Wabitsch, Martin; Behre, Hermann M.
Abstract: Late-onset hypogonadism (LOH), defined as a combination of low serum testosterone (T) levels in combination with clinical signs and symptoms of androgen deficiency in ageing men, is nowadays a well-characterized disease. Testosterone therapy in males affected by hypogonadism leads to a significant decrease of fat mass. In humans, the exact molecular mechanism of T effects on inhibition of adipogenesis is still unknown. We hypothesized that specific microRNAs could be regulated by androgens which might cause an inhibition of adipogenic differentiation. To confirm this hypothesis, human mesenchymal stem cells and a preadipocyte cell line were differentiated into mature adipocytes and in parallel treated with testosterone and dihydrotestosterone. The expression level of miR-375 was upregulated during adipogenic differentiation and downregulated after androgen treatment. Furthermore, we could show that after androgen treatment the decreased expression of miR-375 led to increased expression levels of adiponectin receptor 2 (ADIPOR2) compared to untreated adipocytes. Moreover, inhibition of miR-375 also mediated a decreased adipogenic differentiation and increased ADIPOR2 expression levels. In summary, we identified miR-375 as an androgen regulated microRNA, which could play an important role for understanding the mechanism of the increase in visceral fat mass and the associated insulin resistance caused by testosterone deficiency. Highlights: Androgens inhibit adipogenic differentiation of mesenchymal progenitor cells. In response to androgenic stimulus, alterations in the microRNA expression are induced. Human adiponectin receptor 2 is a target of androgen-repressed miR-375. Both are factors in androgen-dependent inhibition of adipogenesis.